GAMBARAN TINGKAT PENGETAHUAN MAHASISWA PROGRAM PENDIDIKAN PROFESI DOKTER FAK. KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA TENTANG REVISED WORLD HEALTH ORGANIZATION ANALGESIC LADDER UNTUK TATALAKSANA NYERI AKUT PASCA BEDAH DI RUMAH SAKIT PENDIDIKAN - LATHIFAH ARDHIAN; MUHAMMAD JALALUDDIN ASSUYUTHI CHALIL (LP2MTBM MAKARIOZ, 2021)
The Revised WHO Analgesic Ladder can be used for acute pain in emergency and postoperative conditions. The researchobjective was to determine the level of knowledge and attitudes of P3D FK UMSU students towards the Revised WHOAnalgesic Ladder as a post-surgical acute pain management in teaching hospitals. Descriptive with aapproach crosssectional, a sample of 144 people from P3D FK UMSU students batch 2015 and 2016. The knowledge level of P3D FKUMSU students who have good knowledge is19 people, moderate is 87 people and 38 people less. The attitudes of P3D FKUMSU students were 7 questions with correct answers and 3 questions with wrong answers. The level of knowledge of P3DFK UMSU students was in the sufficient category as many as 87 people with a GPA of 3.00 and in the attitude study, 7questions were obtained with correct answers.